Dynamic communication performance of the TESH network under nonuniform traffic patterns - Rahman, M.M. Hafizur; Inoguchi, Yasushi; Sato, Yukinori; Miura, Yasuyuki; Horiguchi, Susumu (Academy Publisher, 2009)

(untitled)
Interconnection networks play a crucial role in the performance of massively parallel computer systems. Hierarchical interconnection networks provide high performance at low cost by exploring the locality that exists in the communication patterns of massively parallel computer systems. The Tori-connected mESH (TESH) Network is a 2D-torus network of multiple basic modules, in which the basic modules are 2D-mesh networks that are hierarchically interconnected for higher level networks. In this paper, we evaluate the dynamic communication performance of the TESH network using dimension order routing algorithm under various nonuniform traffic patterns. We present a proof that the routing algorithm for the TESH network is deadlock free using $2$ virtual channels -- $2$ being the minimum number for dimension-order routing. We evaluate the dynamic communication performance of TESH, mesh, and torus networks by computer simulation. It is shown that the dynamic communication performance of the TESH network is better than that of the mesh and torus networks.